Rationale for a Neisseria gonorrhoeae Susceptible–only Interpretive Breakpoint for Azithromycin. (9th April 2019) - Kersh, Ellen N; Allen, Vanessa; Ransom, Eric; Schmerer, Matthew; Cyr, Sancta; Workowski, Kim; Weinstock, Hillard; Patel, Jean; Ferraro, Mary Jane
Abstract: Background: Azithromycin (AZI) is recommended with ceftriaxone (CRO) for treatment of uncomplicated gonococcal urethritis and cervicitis in the United States, and an AZI-susceptibility breakpoint is needed. Neither the Food and Drug Administration (FDA) nor the Clinical and Laboratory Standards Institute (CLSI) has set interpretive breakpoints for AZI susceptibility. As a result, AZI antimicrobial susceptibility testing (AST) cannot be interpreted using recognized standards. This has contributed to increasingly unavailable clinical laboratory AST, although gonorrhea is on the rise with >550 000 US gonorrhea cases reported to the Centers for Disease Control and Prevention in 2017, the highest number of cases since 1991. Methods: This article summarizes the rationale data reviewed by the CLSI in June 2018. Results: The CLSI decided to set a susceptible-only interpretive breakpoint at the minimum inhibitory concentration of ≤1 µg/mL. This is also the epidemiological cutoff value (ECV) (ie, the end of the wild-type susceptibility distribution). This breakpoint presumes that AZI (1-g single dose) is used in an approved regimen that includes an additional antimicrobial agent (ie, CRO 250 mg, intramuscular single dose). Conclusions: Having a breakpoint can improve patient care and surveillance and allow future development and FDA regulatory approval of modernized AST to guide treatment. The breakpoint coincides with a European Committee on AST decision to remove previously established, differing AZI breakpoints and use the ECV as guidance for testing. The CLSI breakpoint is now the recognized standard that defines AZI susceptibility for gonococcal infections. Abstract : This article summarizes the rationale data that led to the recent Clinical and Laboratory Standards Institute decision to set a susceptible-only interpretive breakpoint for Neisseria gonorrhoeae and azithromycin at a minimum inhibitory concentration equal to or below 1 µg/mL.